Integrating ZBus into Zephyr RTOS: An Experience Report of Knowledge Transfer from Academia to Industry Through Open-Source Contributions - Peixoto, Rodrigo; Teixeira, Leopoldo; Fonseca, Baldoino (Journal of the Brazilian Computer Society, 2026)
Embedded systems are present in a wide range of products, and advances in the Internet of Things, wireless sensor networks, and cyber-physical systems have increased their use. This growth has made embedded software more complex, requiring new real-time operating systems, development kits, libraries, and platforms. Despite these tools, the need for better software engineering practices remains a significant issue in embedded software, to prevent lower software quality and increased maintenance costs. To make matters worse, the knowledge transfer of research advances from academia to industry is still challenging. This paper presents ZBus, an advanced software bus that enables many-to-many communication between threads, enhancing modularity and decoupling in embedded software development. ZBus is a result of a collaborative effort between industry and academia. We also detail the development process, the challenges encountered, the lessons learned, and the collaborative efforts that culminated in integrating ZBus into the widely adopted Zephyr real-time operating system. This integration serves as an experience report on technological knowledge transfer from academia to industry through open-source contributions, as well as a practical guide for researchers and practitioners seeking to engage with industrial open-source initiatives in the embedded software domain.